SRG/eROSITA status and operations during the first four all-sky surveys - Coutinho, D.; Ramos-Ceja, M. E.; Dennerl, K.; Haberl, F.; Meidinger, N.; Merloni, A.; Predehl, P.; Stewart, I.; Freyberg, M.; Bornemann, W.; Brunner, H.; Burwitz, V.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the soft X-ray scientific payload on board the SRG (Spektrum-Roentgen-Gamma) mission. It was successfully launched from Baikonur in July 2019. Following a 101 days cruise phase, SRG reached its final orbit around the Sun-Earth Lagrangian point L2, from where it has carried out already four full-sky surveys. eROSITA is a complex instrument composed of seven identical co-aligned X-ray telescopes with a focal length of 1600mm and an aperture of 350mm. Each telescope is equipped with an independent CCD camera. The cold redundant ITC (Interface and Thermal Controller) manages all seven cameras as well as the thermal control of the telescope and the interface to the spacecraft. The cruise phase of SRG was used to verify that all systems had survived launch and no degradation in the functionality was present. Following that, the main science mission, comprised of an early Calibration and Performance Verification Phase, followed by the all-sky survey. This paper presents the performance of the eROSITA telescope during the first four complete all-sky surveys. It presents the challenges encountered during the telescope operations as well as the operations and mitigation strategies put in place to understand or minimize the effects of the space environment in L2, such as micrometeoroid hits and radiation damage of the detectors.
CRIS-Team Scopus Importer:2022-11-04
Keywords: all-sky survey; eROSITA; L2; operations; space telescope; Spectrum-Roentgen-Gamma; SRG; X-ray telescope